Topical benzoyl peroxide application on the shoulder reduces Propionibacterium acnes: a randomized study - Scheer, Vendela M.; Bergman Jungeström, Malin; Lerm, Maria; Serrander, Lena; Kalén, Anders (Journal of shoulder and elbow surgery, 2018)
Propionibacterium acnes is a common cause of infection following shoulder surgery. Studies have shown that standard surgical preparation does not eradicate P acnes. The purpose of this study was to examine whether topical application of benzoyl peroxide (BPO) gel could decrease the presence of P acnes compared with today's standard treatment with chlorhexidine soap (CHS). We also investigated and compared the recolonization of the skin after surgical preparation and draping between the BPO- and CHS-treated groups. In this single-blinded nonsurgical study, 40 volunteers—24 men and 16 women—were randomized to preoperative topical treatment at home with either 5% BPO or 4% CHS on the left shoulder at the area of a deltopectoral approach. Four skin swabs from the area were taken in a standardized manner at different times: before and after topical treatment, after surgical skin preparation and sterile draping, and 120 minutes after draping. Topical treatment with BPO significantly reduced the presence of P acnes measured as the number of colony-forming units on the skin after surgical preparation. P acnes was found in 1 of 20 subjects in the BPO group and 7 of 20 in the CHS group (P = .044). The results remained after 2 hours (P = .048). Topical preparation with BPO before shoulder surgery may be effective in reducing P acnes on the skin and preventing recolonization.